A scRNA-seq Approach to Identifying Changes in Spermatogonial Stem Cell Gene Expression Following in vitro Culture - De Oliveira, Camila Salum; Nixon, Brett; Lord, Tessa (Frontiers in Cell and Developmental Biology, 2022)
Spermatogonial stem cell function (SSC) is essential for male fertility, and these cells hold potential therapeutic value spanning from human infertility treatments to wildlife conservation. As in vitro culture is likely to be an integral component of many therapeutic pipelines, we have elected to explore changes in gene expression occurring in undifferentiated spermatogonia in culture that may be intertwined with the temporal reduction in regenerative capacity that they experience. Single cell RNA-sequencing analysis was conducted, comparing undifferentiated spermatogonia retrieved from the adult mouse testis with those that had been subjected to 10 weeks of in vitro culture. Although the majority of SSC signature genes were conserved between the two populations, a suite of differentially expressed genes were also identified. Gene ontology analysis revealed upregulated expression of genes involved in oxidative phosphorylation and oxidative stress in cultured spermatogonia, along with downregulation of integral processes such as DNA repair and ubiquitin-mediated proteolysis. Indeed, our follow-up analyses have provided the first depiction of a significant accumulation of ubiquitinated proteins in cultured spermatogonia, when compared to those residing in the testis. The database produced in this manuscript will provide a valuable platform for future studies looking to improve SSC culture approaches and assess their safety for utilisation in therapeutic pipelines.